2004
DOI: 10.1016/s0035-9203(03)00041-5
|View full text |Cite
|
Sign up to set email alerts
|

Compliance with 14-day primaquine therapy for radical cure of vivax malaria—a randomized placebo-controlled trial comparing unsupervised with supervised treatment

Abstract: The only available treatment that can eliminate the latent hypnozoite reservoir of vivax malaria is a 14 d course of primaquine (PQ). A potential problem with long-course chemotherapy is the issue of compliance after clinical symptoms have subsided. The present study, carried out at an Afghan refugee camp in Pakistan, between June 2000 and August 2001, compared 14 d treatment in supervised and unsupervised groups in which compliance was monitored by comparison of relapse rates. Clinical cases recruited by pass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
59
0
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 62 publications
(65 citation statements)
references
References 13 publications
3
59
0
2
Order By: Relevance
“…prolonged treatment courses are associated with poor compliance (27,28). Since the total dose of, rather than duration of exposure to, PMQ determines the efficacy of radical cure (2, 29, 30), abbreviated treatment courses have been developed.…”
Section: Figmentioning
confidence: 99%
“…prolonged treatment courses are associated with poor compliance (27,28). Since the total dose of, rather than duration of exposure to, PMQ determines the efficacy of radical cure (2, 29, 30), abbreviated treatment courses have been developed.…”
Section: Figmentioning
confidence: 99%
“…Park and Kang (162) measured only a 32% effectiveness of postexposure presumptive therapy with the 15-mg daily (14-day) regimen for tens of thousands of soldiers from the Republic of Korea. The 30-mg daily (14-day) regimen achieved 94% efficacy in the northwestern frontier of Pakistan (135), whereas a supervised regimen of 15 mg daily achieved only 48% efficacy in the first 3 months in the same region (133). Another study in the same region recorded a 35% efficacy for that regimen (187 Risk of reinfection may confound these studies from India, Pakistan, and Afghanistan with long-term follow-up (9 to 12 months).…”
Section: Distributionmentioning
confidence: 99%
“…One study showed comparable efficacy of the 14-day course following strong health messaging and clear instructions for completion of the course in Afghan refugees in Pakistan. 111 Short-course, high-dose regimens have potential to increase patient adherence, and thus effectiveness, 112 but appropriately powered prospective multicentered randomized controlled trials are needed to assess the tolerability, safety, efficacy, and effectiveness of such alternative radical curative regimens against current best practice.…”
mentioning
confidence: 99%